Experimental Investigation on the Performance of a Dehumidifier Constructed from a Water-to-Air Heat Exchanger Coated with Composite Desiccant of Mesoporous Silica Gel and LiCl - Srimuk, Jintana; Chirarattananon, Surapong; Chaiwiwatworakul, Pipat; Nathakaranakule, Adisak; Rakkwamsuk, Pattana; Chiarakorn, Siriluk (Applied Science and Engineering Progress, 2023)
Thermal environment in buildings in hot climate is conditioned for comfort by air-conditioning that is energy intensive. Presently, most air-conditioning systems in Thailand and other countries in Southeast Asia use electricity-driven vapor compression systems to cool down the air to the set-point temperature. However, latent load due to condensation of air humidity forms a large part of the air-conditioning load. This paper presents the results of experiments on a dehumidifier constructed from a water-to-air heat exchanger coated with a composite desiccant of large-pore mesoporous silica gel and LiCl, regenerated by low-temperature hot water. Moisture removal capacity (MRC), dehumidification capacity (DC), thermal coefficient of performance (COPth), and an equivalent air conditioning load of dehumidification (EALD) are comparative quantitative parameters derived from experimental results and are studied in this research. The composite desiccant requires low-temperature water for regeneration and offers a higher rate of vapor adsorption and desorption that leads to a shorter required desiccant dehumidification cycle time. The results demonstrate that the dehumidifier is able to effectively reduce moisture in ventilation air and substantially reduces the cooling load of air-conditioning.